KEJAHATAN GENOSIDA DALAM KETENTUAN HUKUM NASIONAL SEBAGAI KEJAHATAN TRADISIONAL - Hetty Hassanah (Maleo Law Journal, 2017)
International crimes are acts that are internationally recognized as international crimes. Based on the Rome Statute of 1998 on the International Criminal Court one of the international crimes is genocide that is every act committed with the aim of destroying all or part of a certain national, ethnic, racial or religious group in various ways including: killing the group, causing injury or mental seriously against members of the group, deliberately raising the living conditions of the group calculated to cause physical destruction as a whole or in part, imposing measures intended to prevent birth in the group or forcibly transferring children of that group to other groups.Keywords : Genocide, Transnational Crime